Neuroinflammation in Prion Disease - Li, Bei (Int J Mol Sci, 2021)
Neuroinflammation, typically manifest as microglial activation and astrogliosis accompanied by transcriptomic alterations, represents a common hallmark of various neurodegenerative conditions including prion diseases. Microglia play an overall neuroprotective role in prion disease, whereas reactive astrocytes with aberrant phenotypes propagate prions and contribute to prion-induced neurodegeneration. The existence of heterogeneous subpopulations and dual functions of microglia and astrocytes in prion disease make them potential targets for therapeutic intervention. A variety of neuroinflammation-related molecules are involved in prion pathogenesis. Therapeutics targeting neuroinflammation represents a novel approach to combat prion disease. Deciphering neuroinflammation in prion disease will deepen our understanding of pathogenesis of other neurodegenerative disorders.